Exploring Biology Students’ Critical Thinking Using Mind Maps - Nita Nuraini; Rindi Novitri Antika (Postgraduate, University of Mataram, 2024)
Critical thinking is one of the 21st-century skills that is important for students to have, because this ability is useful for developing knowledge, evaluating and connecting with facts or information from various sources. Critical thinking skills can be trained by implementing innovative learning strategies, including mind maps. This research aims to explore the critical thinking skills of biology students using mind maps. The type of experimental research used is a pre-experimental design. Treatment of research subjects was carried out without a control group. The research was conducted on biology students taking Human Physiology courses. The research results show that students' critical thinking skills are included in the very good category for the interpretation indicator (80.77) and the good category for the analysis, inference, evaluation, explanation and self-regulation indicators (75.00; 72.12; 71.15; 75.00; 74.00). Based on the results, using mind maps in learning helps students improve critical thinking skills.